Otto-Schmidt-Labor für Polar- und Meeresforschung : Schlussbericht - Alfred-Wegener-Institut Für Polar- Und Meeresforschung; Otto-Schmidt-Laboratory For Polar And Marine Research, Sankt Petersburg (Technische Informationsbibliothek u. Universitätsbibliothek, 2003)
Ill., graph. Darst., Kt ... : (de)Russian-German cooperation in the field of marine and polar research, climate research in the Siberian Arctic ...